ANALISA DATA DAN MASALAH DALAM PERANCANGAN INTERFACE e-LOCATION kAFE - ANISYA ANISYA; Dede Wira Trise Putra (Fakultas Teknik dan Ilmu Komputer (FASTIKOM) UNSIQ, 2022)
Payakumbuh has a population of 78,702 people with teenagers and adults, which makes many internet cafe businesses appear with a very attractive and comfortable internet cafe display design and good facilities. This makes people hesitate in choosing which cafe they want to visit because cafes with a nice and comfortable appearance must have expensive menu prices. And there are people who get information about the internet cafe from the information circulating in the surrounding environment with the appropriate appearance and the right price for themselves but do not know where the internet cafe is. So the purpose of this research is to design a web site-based interface for the map page of the spread of internet cafes and important information pages for internet cafes in the city of Payakumbuh. The method used is a system life cycle with a focus on problem analysis and data obtained from the results of literature studies, interviews, and observations. The results obtained from this study are in the form of an e-location cafe system interface design.